Pemberian Rizobakteri dan Coumarin pada Pertumbuhan dan Pembentukan Umbi Tanaman Kentang (Solanum tuberosum L) - Sari, Henny Puspita; ,, Warnita; Dwipa, dan Indra (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Increasing the productivity of potato crops will require the availability of tubers that are of high quality and resistantto disease. Giving isolates rhizobacteria and coumarin is expected to increase the growth and formation of potato tubers.The purpose of this study was to obtain the best types of rhizobacteria and coumarin concentrations in increasing theproductivity of potato plants. The research was conducted in the experimental garden of the Center for Technology Transferand Agricultural Zone Development of Andalas University, Alahan Panjang, Solok Regency, West Sumatra, from October2016 to January 2017. The study used a 2-factor complete randomized design with three replications. The first factor wasrhizobacterial isolates, namely without bacteria, BT.4.1 isolates, BT.4.2 isolates, BT.4.3 isolates. The second factor was theconcentration of coumarin growth inhibitors, namely 0, 50, 100, and 150 mg L-1. The parameters observed were morphologicalcharacterization rhizobacteria, leaf area, relative growth rate, growth rate potato tubers at 1-month-old, fresh weight oftubers aged 100 days after planting, tuber classes, namely: large, medium and small. Observation data were analyzed bythe F test, followed by the HSD test at 5% level. The results showed that BT4.1 and BT.4.2 rhizobacteria with coumarin 100mg L-1 and 150 mg L-1 increased the growth of potato plants, while the results of potato plants were more affected by theapplication of BT.4.1 and BT rhizobacteria.